2006
DOI: 10.1111/j.1478-3231.2006.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver protection by hypothermic perfusion at different temperatures during total vascular exclusion

Abstract: HP at 20 degrees C is equally effective in preserving liver function and preventing hepatocellular injury under TVE as compared with HP at 28 degrees C. HP at 28 degrees C is advised, because of the lesser perfusion volume necessary for cooling of the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…It was further shown that the protective effects of hypothermia were optimal when ischemic livers were cooled to 26°C, whereas lower temperatures did not impart additional hepatoprotection (29). This finding is in line with other reports (30) and suggests that a relatively modest decrease in liver temperature during ischemia is sufficient to reduce I/R injury. It is important to underscore, the same metabolic responses to ischemia, including succinate buildup, were more pronounced in ischemic livers than in other ischemic organs (heart, kidney) (11).…”
Section: Mitochondrial Metabolismsupporting
confidence: 81%
See 1 more Smart Citation
“…It was further shown that the protective effects of hypothermia were optimal when ischemic livers were cooled to 26°C, whereas lower temperatures did not impart additional hepatoprotection (29). This finding is in line with other reports (30) and suggests that a relatively modest decrease in liver temperature during ischemia is sufficient to reduce I/R injury. It is important to underscore, the same metabolic responses to ischemia, including succinate buildup, were more pronounced in ischemic livers than in other ischemic organs (heart, kidney) (11).…”
Section: Mitochondrial Metabolismsupporting
confidence: 81%
“…At 24 h of reperfusion, improved hepatic microcirculatory perfusion, less endothelial injury and reduced lipid peroxidation were seen after IHP compared to THVE alone (76). In a similar study using 60 min of THVE, survival in the IHP groups (28°C or 20°C liver temperature) was 100% compared with 66% in normothermic THVE controls (30). Moreover, the use of IHP preserved bile production and reduced AST and IL-6 levels.…”
Section: Hepatocyte Transportersmentioning
confidence: 59%
“…As a result of that, energy supplies are preserved, the amount of oxidative stress is reduced, and the detrimental late inflammatory response characteristic of I/R injury is hampered [40,41] . Overall, these effects result in better postoperative recovery, as has been shown by a series of experimental studies conducted in our surgical laboratory [42][43][44][45] .…”
Section: Thve (Combined With Cold Perfusion)mentioning
confidence: 65%
“…Although the human liver might tolerate ischemia better than excessive blood loss, the adverse effects of ischemia should not be disregarded. The damage incurred by post-ischemic reperfusion to the liver parenchymal cells and the microvascular system are well established, both in experimental studies as well as in clinical studies [26, 49, 59, 60]. Especially in livers with pre-existent disease such as cirrhosis or steatosis, the injurious effects of ischemia/reperfusion injury have shown to be enhanced [61].…”
Section: Discussionmentioning
confidence: 99%